Doctor-patient communication as a determining parameter in the provision of health care - Tsounis, A.; Sarafis, Pavlos (My University, 2014)
© Athens Medical Society. Doctor-patient communication is a determining element in the quality of health care. This is a review of the factors that affect this communication and their impact on the final therapeutic outcome. Firstly, the various different theoretical approaches to the doctor-patient relationship are presented. Following this, some of the main obstacles to physician-patient communication are reported, and finally the ways in which these barriers affect the adherence of patients to the therapeutic requirements are examined. Particular attention is given to the role of empathy and its importance as a factor in the improvement of the therapeutic relationship, patient satisfaction and compliance with medical instructions. Based on the above review, a series of proposals concerning the necessity of continuing medical education in communication skills are suggested.
Keywords: Communication; Doctor-patient relationship; Empathy; Medical education